PENULISAN ARTIKEL ILMIAH UNTUK GURU SEKOLAH DASAR SE-KABUPATEN BANGKA - Sri Sugiyarti; Nur Fitriani; Rajab Vebrian (Jurnal Pengabdian UntukMu NegeRI, 2019)
Writing article is an absolute requirement for teachers who will rise in rank and certain classes. In the fact, there are so many teachers to retirees only in the IV / a. The main problem is about credit numbers from sub-elements of scientific publications and / or elements of innovative work. This workshop aims to provide an understanding for elementary school teachers in writing article. The method used is a workshop that was held for two days with a total of 32 hours of learning hours. The results obtained from this workshop were an increase in teacher understanding of writing article and producing article papers from the teacher.